EFEKTIVITAS PERINGATAN GAMBAR BAHAYA MEROKOK DALAM MENGURANGI PENGGUNAAN ROKOK PADA REMAJA DI SMP 4 PAREPARE - Wahyuni Ahmad; Rahman; Muh. Iqra Taufan; Andi Dian Fitriana; Abd. Rahman (Rumah Jurnal STAIN Majene, 2022)
The phenomenon of smoking in Indonesia is indeed very concerning, smoking is a problem that has not been resolved until now the main smoking among teenagers, therefore the purpose of this study was to determine the effectiveness of warning images of the dangers of smoking for adolescents in SMP 4 Parepare City. The research method used by the researcher is a quantitative research method with a single subject approach. As for the way to obtain data that is in accordance with the method and type of this research, the data collection technique is by means of questionnaires and documentation, with the selection of respondents using purposive sampling technique. The data analysis technique refers to the technique developed by Secord and Backman. The results of this study indicate that giving scary pictures in the form of warning pictures of the dangers of smoking is effective in influencing attitudes towards smoking behavior among adolescents at SMP 4 Parepare City. For researchers who want to research the same research, it is better if the treatment is not done once but repeatedly to get more effective results in the research that we do on several subjects.